Pa(ng)labas architecture + cinema :projections of Filipino space in film - Lico, Gerard Rey A. (National Commission for Culture and the Arts, 2009)
PA(ng)LABAS is doubly coded to encompass both the concepts of projected moving image (palabas) and the exteriority of architecture (panglabas). Both post a sense of place, a sense of locus. The collection of images showcased in this compendium dramatizes the juxtaposition of architecture and the imagery environment of the cinema, and at the same time, probes the transformation of Filipino space, architecture, and urban landscape as visualized and mediated through the cinematic lens.